Experimental Validation of Gravitational Acceleration Measurement Using Kater’s Reversible Pendulum - Tyas Nisa Fadilah; Niswatul Kariimah; Chilwatun Nasiroh; Habibah Khusna Baihaqi; Dyah Arum Arimurti (Department of Physics Education, Universitas Mataram, 2026)
The measurement of gravitational acceleration is a fundamental experiment in physics education, providing essential understanding of classical mechanics and experimental techniques. This study presents the experimental validation of gravitational acceleration measurement using a low-cost Kater’s reversible pendulum developed for laboratory applications. The apparatus consists of two knife-edge pivots and adjustable masses that enable nearly identical oscillation periods about both pivot points. Oscillation periods were measured for various positions of the movable mass, while sensor-based measurements were used for verification. The equal-period condition was determined analytically from the experimental data and used to calculate the local gravitational acceleration. The measured value was (9.768 ± 0.012) m s⁻², where the uncertainty was estimated using partial differential error propagation based on instrumental uncertainties in length and time measurements. The result shows good agreement with the accepted local gravitational acceleration, with a relative deviation of approximately 0.13%. These findings demonstrate that the developed Kater’s reversible pendulum can provide reliable measurements of gravitational acceleration and is suitable for undergraduate physics laboratories. Accurate determination of gravitational acceleration was found to depend primarily on achieving equal oscillation periods and precise determination of the effective pendulum length.